Idiopathic subglottic stenosis: a review - Aravena, Carlos; Almeida, Francisco A.; Mukhopadhyay, Sanjay; Ghosh, Subha; Lorenz, Robert R.; Murthy, Sudish C.; Mehta, Atul C. (Journal of Thoracic Disease; Vol 12, No 3 (March 23, 2020): Journal of Thoracic Disease, 2020)
Idiopathic subglottic stenosis (iSGS) is a fibrotic disease of unclear etiology that produces obstruction of the central airway in the anatomic region under the glottis. The diagnosis of this entity is difficult, usually delayed and confounded with other common respiratory diseases. No apparent etiology is identified even after a comprehensive workup that includes a complete history, physical examination, pulmonary function testing, auto-antibodies, imaging studies, and endoscopic procedures. This approach, however, helps to exclude other conditions such as granulomatosis with polyangiitis (GPA). It is also helpful to characterize the lesion and outline management strategies. Therapeutic endoscopic procedures and surgery are the most common management modalities, but medical therapy can also play a significant role in preventing or delaying recurrence. In this review, we describe the morphology, pathophysiology, clinical presentation, evaluation, management, and prognosis of iSGS.